The Use of an open-ended learning model in kanji courses to improve the ability to master kanji sub-characters - Alo Karyati; Paramita Winny Hapsari (Japanese Research on Linguistics, Literature, and Culture, 2026)
Kanji is the most complicated subject in learning Japanese. One of the difficulties in forming kanji is the sub-character kanji. Sub-character kanji is a sorting or breaking of the pull contained in a kanji. Because of this difficulty, a learning model is needed in the learning process that can help improve students' ability to understand how sub-characters in each kanji are studied. students. The Open-Ended Learning model is a solution to solving the problem of learning sub-character kanji. The objectives of this study are: (1) to determine students' ability to master sub-character kanji before using the OEL/open-ended learning model, and (2) to determine students' ability to master sub-character kanji after using the OEL/open-ended learning model. (3) to determine the difference in students' mastery of sub-character kanji before and after using the open-ended learning model, (4) to determine students' difficulties in learning sub-character kanji. The type of this research is a mixed method, which combines quantitative and qualitative research types. The population and sample in this study were 33 semester students. The data analysis technique in this study uses a qualitative descriptive approach. The results of this study are that students' ability to master kanji sub-characters has increased, and students understand how a kanji can be formed into its smallest part. It is hoped that after this research, the open-ended learning model can be applied to other Japanese language courses.